The psychological stress response of COVID-19 to medical staff and prevention: A large sample study from China - Hu, Mei; Xu, Yuan; Bu, Dengying; Luo, Kai; Chang, Liying; Mao, Chun (Frontiers in Psychology, 2023)
Objectives: In the face of the COVID-19 pandemic, medical staff in China were more likely to suffer from psychological problems. By investigating the actual state of psychological stress response of medical staff during the COVID-19 outbreak, the study discussed and analyzed the influencing factors of different psychological states in order toprevent the occurrence of serious adverse emotional events in medical staff. Methods: In the Xiangyang Central Hospital, 1,466 medical staff members have adopted the Psychological Questionnaire for Emergencies Events of Public Health (PQEEPH), which includes questions about depression, neurasthenia, fear, obsessive anxiety, and hypochondriac disorders. The questionnaire also asks about gender, age, education level, health, department, position, and whether a personnel exposure history correlation analysis has been confirmed. Results: The survey revealed that 55% had depression, 26.7% had neurasthenia, 95% had fear, 47.9% had obsessive anxiety, and 69.3% had hypochondria. The effects of depression and hypochondriac emotional stress were significantly greater in female workers than in male workers (P<0.05). Those with higher educational levels had a stronger emotional stress response. Medical professionals with or without contact histories, those who were suspected or confirmed, as well as those in various positions and departments, all demonstrated significant differences in their stress emotions (P<0.05). Conclusions: Emotional stress affected medical professionals, especially doctors and nurses, who were on the front lines of clinical work in the face of significant public health emergencies. Therefore, to reduce the stress burden and enhance mental health on medical staff, hospitals were suggested to improve their emergency management practices. In addition, the sensitization knowledge training and psychological counseling for front-line clinical staff should be strengthened.